Dukungan Sosial Keluarga dan Tingkat Kecemasan Penderita TB Paru di Puskesmas Kambaniru Kabupaten Sumba Timur - Domianus Namuwali; Maria Kareri Hara; Yosephina E.S Gunawan (FORIKES, 2020)
Background: Tuberculosis or TB was the main cause of death in infectious diseases. In 2017 there were 1.3 deaths due to TB. Globally, it was estimated that the incidence of TB disease was around 10.0 million and most prevalent in men around 5.8 million. Approximately 90% of TB patients were found in adults above 15 years old. In 2018, the number of TB sufferers in Kambaniru health center was 31 people. Objective: The purpose of this study was to identify the correlation of family social support towards the anxiety of TB patients in Kambaniru Health Center, East Sumba Regency. Methods: The research method used was a quantitative method with cross sectional design. The sampling was taken by using a total sampling technique with a sample size of 31 respondents. This research was conducted in Kambaniru Health Center from August to September 2019. Results: The results of this study found that the most respondents had moderate anxiety as many as 16 people (51.6%), the most family social support was good as many as 20 respondents (64.4%) and from the Spearman Correlation Test it was found that there was no significant correlation between family social support and the level of anxiety of TB patients in Kambaniru Health Center. Conclusion: There was no correlation between family social support and anxiety level of TB patients in Kambaniru Health Center. Keywords: family social; support, anxiety level; TB patients ABSTRAK Latar belakang: PenyakitTB Paru merupakan penyebab utama kematian pada penyakit infeksi, Pada tahun 2017 terdapat 1,3 kematian akibat penyakit TB. Secara global diperkirakan insiden penyakit TB Paru sekitar 10,0 juta dan paling banyak ditemukan pada laki-laki sekitar 5,8 juta. sekitar 90% Penderita TB Paru ditemukan pada usia dewasa ≥ 15 tahun. Pada tahun 2018 jumlah penderita TB paru di Puskesmas Kambaniru sebanyak 31 orang. Tujuan: Tujuan dari penelitian untuk mengidentifikasi hubungan dukungan social keluarga terhadap kecemasan pada penderita TB paru di Puskesmas Kambaniru Kabupaten Sumba Timur. Metode: Metode penelitian yang digunakan kuantitatif dengan rancangan cross sectional. Pengambilan sampel dilakukan dengan teknik total sampling dengan ukuran sampel 31 responden. Penilitian ini dilaksanakan di Puskemas Kambaniru pada Bulan Agustus – September 2019. Hasil: Hasil dari penelitian ini didapatkan bahwa sebagian besar responden mengalami kecemasan sedang sebanyak 16 orang (51,6%), Dukungan sosial keluarga terbanyak adalah baik sebanyak 20 responden (64,4%) dan dari hasil Uji Korelasi Spearman didapatkan tidak ada hubungan yang signifikan dukungan social keluarga dengan tingkat kecemasan penderita TB Paru di Puskesmas Kambaniru. Kesimpulan: Tidak ada hubungan dukungan social keluarga dengan tingkat kecemasan penderita TB paru di Puskesmas Kambaniru. Kata kunci: dukungan sosial keluarga; tingkat kecemasan; penderita TB